3(8-x)-5=-6x-4+3n

Simple and best practice solution for 3(8-x)-5=-6x-4+3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(8-x)-5=-6x-4+3n equation:


Simplifying
3(8 + -1x) + -5 = -6x + -4 + 3n
(8 * 3 + -1x * 3) + -5 = -6x + -4 + 3n
(24 + -3x) + -5 = -6x + -4 + 3n

Reorder the terms:
24 + -5 + -3x = -6x + -4 + 3n

Combine like terms: 24 + -5 = 19
19 + -3x = -6x + -4 + 3n

Reorder the terms:
19 + -3x = -4 + 3n + -6x

Solving
19 + -3x = -4 + 3n + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
19 + -3x + 6x = -4 + 3n + -6x + 6x

Combine like terms: -3x + 6x = 3x
19 + 3x = -4 + 3n + -6x + 6x

Combine like terms: -6x + 6x = 0
19 + 3x = -4 + 3n + 0
19 + 3x = -4 + 3n

Add '-19' to each side of the equation.
19 + -19 + 3x = -4 + -19 + 3n

Combine like terms: 19 + -19 = 0
0 + 3x = -4 + -19 + 3n
3x = -4 + -19 + 3n

Combine like terms: -4 + -19 = -23
3x = -23 + 3n

Divide each side by '3'.
x = -7.666666667 + n

Simplifying
x = -7.666666667 + n

See similar equations:

| 3x-10+2x=-65 | | t(n)=-6+3(447-1) | | 4(6-9)/6= | | 8-(-4)2-5= | | 5b-b-1=7 | | 2qt=c | | 8x+3y=37 | | 3(t)=67-16t^2 | | p(x)=5x^2-3x+2 | | t(n)=24-5(447) | | 19w-9w-9w+3=20 | | 8x=37-3y | | -3x+3=2x | | (3x+1)(1x+2)= | | 8n=15model | | Xy=126 | | 14n-13n=15 | | 8n=15midel | | 5h+4=34 | | 12/(1/9) | | -2/3(5/6x-3)= | | t(n)=5(447)-3 | | 7/8x=14/40 | | -2/5-7/10= | | 16k+k-14k-2=16 | | 4(1/9) | | -2x^2+2x+17=0 | | 0.02x+0.07(7000-x)=320 | | 3x^2/3-11x^1/2-4=0 | | -2w-5/2=7/5w-6/5 | | y=8x-4x | | x^3+8x^2+22x+20=0 |

Equations solver categories